Analysis of Postprandial Glycemia in Relation to Metabolic Compensation and Other Observed Parameters of Outpatients with Type 2 Diabetes Mellitus in the Czech Republic - Žďárská, Denisa Janíčková; Hill, Martin; Kvapil, Milan; Piťhová, Pavlína; Brož, Jan (Diabetes therapy, 2018)
INTRODUCTION: The goal of the study was to determine the level of metabolic compensation expressed by glycosylated hemoglobin, fasting plasma glucose, and postprandial glucose as determined after a standardized breakfast; further, to evaluate interrelationships between the studied parameters and postprandial glucose levels. METHODS: The study included 1055 patients with type 2 diabetes mellitus. Their fasting plasma glucose and postprandial glucose were measured before and after a standardized breakfast. Attending diabetologists completed a uniform questionnaire that included demographic data, type of antidiabetic treatment, duration of diabetes, latest glycosylated hemoglobin value, presence of dyslipidemia, and organic complications. RESULTS: Glycosylated hemoglobin < 53 mmol/mol was achieved in 363 (34.2%), postprandial glucose < 7.5 mmol/l in 211 (19.9%), and fasting plasma glucose < 6 mmol/l in 251 (23.7%) patients. Excellent metabolic compensation, indicated by all the above mentioned glycosylated hemoglobin, fasting plasma glucose, and postprandial glucose values simultaneously, was achieved in only 71 (6.7%) patients. Comparable to fasting plasma glucose and postprandial glucose values, correlation with glycosylated hemoglobin levels is statistically significant; however, there is no difference at different glycosylated hemoglobin levels. There was a significant correlation between dyslipidemia and postprandial glycemia (p = 0.013). CONCLUSION: The objective of care for patients with diabetes mellitus is to improve their long-term metabolic compensation; to that end, both fasting plasma glucose and postprandial glucose deserve equal attention.
Keywords: Metabolic compensation; Diabetes mellitus; Fasting glycemia; Glycosylated hemoglobin; Postprandial glycemia